2021
DOI: 10.1126/sciadv.abh2488
|View full text |Cite
|
Sign up to set email alerts
|

Gene-rich UV sex chromosomes harbor conserved regulators of sexual development

Abstract: Nonrecombining sex chromosomes, like the mammalian Y, often lose genes and accumulate transposable elements, a process termed degeneration. The correlation between suppressed recombination and degeneration is clear in animal XY systems, but the absence of recombination is confounded with other asymmetries between the X and Y. In contrast, UV sex chromosomes, like those found in bryophytes, experience symmetrical population genetic conditions. Here, we generate nearly gapless female and male chromosome-scale re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 122 publications
2
80
2
Order By: Relevance
“…However, no sMYB - PRR linkage was detected in these genomes at either short or long distance; many of these genome assemblies are not chromosome-resolved, which could mean the linkage would be missed if it were on the scale found in Amborella . In addition, two chromosome-resolved moss genomes of Physcomitrium patens (formerly Physcomatrella patens ) and Ceratodon purpureus have the sMYB and PRR on separate chromosomes and therefore clearly unlinked (Lang et al, 2018; Carey et al, 2021). A chromosome-resolved genome assembly of a bryophyte is available for Sphagnum angustifolium (formally Sphagnum fallax ), which provides an opportunity to evaluate a third moss genome (Meleshko et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, no sMYB - PRR linkage was detected in these genomes at either short or long distance; many of these genome assemblies are not chromosome-resolved, which could mean the linkage would be missed if it were on the scale found in Amborella . In addition, two chromosome-resolved moss genomes of Physcomitrium patens (formerly Physcomatrella patens ) and Ceratodon purpureus have the sMYB and PRR on separate chromosomes and therefore clearly unlinked (Lang et al, 2018; Carey et al, 2021). A chromosome-resolved genome assembly of a bryophyte is available for Sphagnum angustifolium (formally Sphagnum fallax ), which provides an opportunity to evaluate a third moss genome (Meleshko et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“… 18 Further, haploid plants spontaneously containing both U and V chromosomes develop as females, supporting the presence of a dominant U-linked feminizing locus, 22 in whose absence plants develop as males. Genomic analyses of M. polymorpha have shown that both U and V chromosomes have lower gene densities, and higher repetitive content, than the autosomes, 19 , 20 , 21 similar to the symmetrical changes in other non-recombining U/V systems, in the mosses Ceratodon purpureus 23 and Syntrichia caninervis 24 and the brown alga Ectocarpus . 25 However, the sex-determining genes have yet to be identified in liverworts or any other complex multicellular haploid organism, and only recently has it become possible to study the evolution of sex chromosomes in haploid systems and test their predicted differences from diploid systems.…”
Section: Introductionmentioning
confidence: 82%
“…Although, plant sex chromosomes are not without consequences from suppressed recombination. A consistent pattern found is an enrichment of transposable elements (TEs) and other repeats [65,[76][77][78], which often accumulate in regions of low recombination [79]. In fact, in several species TE expansions have instead driven the Y chromosome to be larger than the X, such as in Coccinia grandis [80] and S. latifolia [81].…”
Section: "The Discovery Referred To In a Preceding Footnote That The Spermatogonial Number Of Anasa Is 21 Instead Of 22 Again Goes Far Tomentioning
confidence: 93%
“…However, some plant sex chromosomes defy these expectations. The moss UV sex chromosomes evolved hundreds of millions of years ago but are homomorphic in Ceratodon purpureus [65]. Similarly, in Cannabis sativa the sex chromosomes share an origin with H. lupulus [62], however, they are instead homomorphic.…”
Section: "The Discovery Referred To In a Preceding Footnote That The Spermatogonial Number Of Anasa Is 21 Instead Of 22 Again Goes Far Tomentioning
confidence: 99%
See 1 more Smart Citation